The Relationship Between Digital Innovation, Digital Marketing, and MSME Performance: The Mediation Role of Processed Fish Environmentally Friendly Supply Chain Management - Nadliroh, Indah Datin; Sudarmiatin, Sudarmiatin (International Journal of Business, Law, and Education, 2024)
This inquire about points to investigate the interceding impact of naturally inviting supply chain administration on the relationship between advanced advancement, advanced showcasing, and the execution of MSMEs in the angle handling division in Gresik. Analysts utilized a cross-sectional investigate technique to collect information from 90 angle handling bungalow industry proprietors through a self-administered overview survey utilizing a doable inspecting procedure. The inquire about strategy employments quantitative and information is prepared utilizing WarpPLS 8.0. Relapse examination discoveries appear that the advanced advancement variable has a noteworthy impact on green supply chain administration with a p-value of 0.24 and a negative beta coefficient esteem, to be specific β = -0.07. Computerized showcasing has a positive and critical impact on progressing green supply chain administration with a p-value <0.001 and a positive β coefficient esteem of β 0.29. Advanced advancement and advanced promoting have a noteworthy impact on progressing the execution of MSMEs with green supply chain administration as intervention with a p-value of 0.09 and a positive beta coefficient esteem of β=0.14